2008
DOI: 10.1007/s11517-008-0347-6
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the general linear model for sensible hemodynamic response function waveforms

Abstract: We propose a method to do constrained parameter estimation and inference from neuroimaging data using general linear model (GLM). Constrained approach precludes unrealistic hemodynamic response function (HRF) estimates to appear at the outcome of the GLM analysis. The permissible ranges of waveform parameters were determined from the study of a repertoire of plausible waveforms. These parameter intervals played the role of prior distributions in the subsequent Bayesian analysis of the GLM, and Gibbs sampling w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…The use of a model-based fNIRI analysis approach by means of the general linear model (GLM) methodology (Bullmore et al, 1996;Friston et al, 1995;Worsley and Friston, 1995) was reported by several authors (e.g. Boas et al, 2003;Çiftçi et al, 2008;Fekete et al, 2011;Hu et al, 2010;Imai et al, 2012;Koh et al, 2007;Moriai-Izawa et al, 2012;Plichta et al, 2007a,b;Schroeter et al, 2004;Tsuzuki et al, 2012;Ye et al, 2009). GLM is a statistical linear model explaining data as a linear combination of an explanatory variable plus an error term.…”
Section: Multivariate Methods Of Typementioning
confidence: 99%
“…The use of a model-based fNIRI analysis approach by means of the general linear model (GLM) methodology (Bullmore et al, 1996;Friston et al, 1995;Worsley and Friston, 1995) was reported by several authors (e.g. Boas et al, 2003;Çiftçi et al, 2008;Fekete et al, 2011;Hu et al, 2010;Imai et al, 2012;Koh et al, 2007;Moriai-Izawa et al, 2012;Plichta et al, 2007a,b;Schroeter et al, 2004;Tsuzuki et al, 2012;Ye et al, 2009). GLM is a statistical linear model explaining data as a linear combination of an explanatory variable plus an error term.…”
Section: Multivariate Methods Of Typementioning
confidence: 99%
“…A stimulus will cause an increase in HbO [4], thus making the signal to rise. If there is no further stimulation, this response will return to the baseline.…”
Section: Regression Model and Statistical Analysismentioning
confidence: 99%
“…Additionally, it is necessary to test whether m 2 of the HbO has returned to near the baseline. And then, to determine whether the obtained HbO was actually caused by the provided stimulus or not, m 1 is computed, see [4,27,32]. If m 1 in a channel is less than or equal to zero, the channel is concluded inactive and is discarded.…”
Section: Regression Model and Statistical Analysismentioning
confidence: 99%
See 2 more Smart Citations